The Romans Debate - Byrskog, Samuel (Svensk exegetisk årsbok, 2025)
This article is an introduction to the conference on Paul’s letter to the Romans held at Lund University 23-24 September 2024. It rehearses some of the published literature during recent years and identifies four current trends: recurring historical issues, recurring theological readings, new hermeneutical readings and apocalyptic.